Processive DNA synthesis is associated with localized decompaction of constitutive heterochromatin at the sites of DNA replication and repair. (1st January 2019) - Chagin, Vadim O.; Reinhart, Britta; Becker, Annette; Mortusewicz, Oliver; Jost, K. Laurence; Rapp, Alexander; Leonhardt, Heinrich; Cardoso, M. Cristina
ABSTRACT: Constitutive heterochromatin is considered as a functionally inert genome compartment, important for its architecture and stability. How such stable structure is maintained is not well understood. Here, we apply four different visualization schemes to label it and investigate its dynamics during DNA replication and repair. We show that replisomes assemble over the heterochromatin in a temporally ordered manner. Furthermore, heterochromatin undergoes transient decompaction locally at the active sites of DNA synthesis. Using selective laser microirradiation conditions that lead to damage repaired via processive DNA synthesis, we measured similarly local decompaction of heterochromatin. In both cases, we could not observe large-scale movement of heterochromatin to the domain surface. Instead, the processive DNA synthesis machinery assembled at the replication/repair sites. Altogether, our data are compatible with a progression of DNA replication/repair along the chromatin in a dynamic mode with localized and transient decompaction that does not globally remodels the whole heterochromatin compartment.